Health services care for adolescents literacy public health for reproductive health at early marriage in North Lampung Regency - Purdalistya, Endah (BKM Public Health and Community Medicine, 2021)
Objective : Adolescence is a transition period from childhood to adulthood. Various problems that occur in adolescents are influenced by various dimensions of life in them, both biological, cognitive, moral and psychological dimensions as well as the influence of the surrounding environment. These include adolescent reproductive health, which involves free sex, extramarital or unwanted pregnancy, abortion, and young marriage. The Central Bureau of Statistics and UNICEF in 2016 reported that 85% of girls in Indonesia end their education after they marry at a young age. This paper aims to explore adolescents' understanding of health on reproductive health issues through adolescent care health services (PKPR). Method: The method used is interviewing PKPR responsible officers and some students as well as literature from journals and online media. Monitoring and evaluating pkpr program. Results : All Puskesmas in the North Lampung Regency have been able to PKPR. PKPR activities in puskesmas have been running with the availability of a special room for counseling so as to provide a privacy space. The next activity is counseling to both junior high and high school. Students have received material about reproductive health in science lessons but only outlines are not in detail. Puskesmas officers have trained peer counselors from several students in each school. Peer counsellors mean that students feel the presence of someone who can understand themselves and feel more comfortable if they convey their complaints to their peers. It was also found that there are some students who are no longer in school because they are married so they decided to drop out. Conclusion : With these problems, it is expected that the pkpr program has a very important role for teenagers. Through this PKPR, teenagers can gain knowledge about health, socializing places, and get health services that pay attention to the needs of teenagers. So that the health problems of adolescents can be minimized.